2022
DOI: 10.1037/emo0001063
|View full text |Cite
|
Sign up to set email alerts
|

Emotion words link faces to emotional scenarios in early childhood.

Abstract: Recent theories have suggested that emotion words may facilitate the development of emotion concepts. The present study investigates whether emotion words affect children's performance on an emotion category learning task. Across two experiments, 72 three-year-old children (49 female) were asked to identify which emotional face best matched particular emotional scenarios during nine pretest and nine posttest trials. The scenarios in the present studies aligned with emotions typically learned among older age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
(75 reference statements)
1
14
0
Order By: Relevance
“…Thus, emotion labels may help children extract statistical regularities in emotion. Indeed, children learn emotion categories more easily when presented with verbal labels (Ogren & Sandhofer, 2022;, verbal abilities relate to the emergence of emotion understanding from childhood to adulthood (Nook et al, 2017), and children begin to correctly match labels and facial expressions at around the same age that they produce emotion labels (i.e., 2 years of age; Frank et al, 2017;Wu et al, 2022). Research has also shown a tight connection between how people think about the similarities of emotion words and how emotion transitions typically unfold (Barrett, 2006;Thornton et al, 2020;Thornton & Tamir, 2017).…”
mentioning
confidence: 99%
“…Thus, emotion labels may help children extract statistical regularities in emotion. Indeed, children learn emotion categories more easily when presented with verbal labels (Ogren & Sandhofer, 2022;, verbal abilities relate to the emergence of emotion understanding from childhood to adulthood (Nook et al, 2017), and children begin to correctly match labels and facial expressions at around the same age that they produce emotion labels (i.e., 2 years of age; Frank et al, 2017;Wu et al, 2022). Research has also shown a tight connection between how people think about the similarities of emotion words and how emotion transitions typically unfold (Barrett, 2006;Thornton et al, 2020;Thornton & Tamir, 2017).…”
mentioning
confidence: 99%
“…Future studies could evaluate how experts in language and emotional knowledge, such as a selected sample of psychotherapists, score on the MOVE. On the other hand, the result that a considerable proportion of items had low difficulty may be useful with participants such as children or adolescents, who are still learning about emotions (Ogren & Sandhofer, 2022), patients with semantic dementia (Lindquist et al, 2014) or persons affected by primary progressive aphasia (Bertoux et al, 2020). Since the RM is an invariant measurement model with the formal property of specific objectivity, item calibration is independent of the sample when data‐model fit is adequate enough, as it is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Theories of constructed emotion (Barrett, 2017; Brooks et al, 2017; Siegel et al, 2018) give language an outstanding role in human emotion science by postulating that changes in the natural world become mental states when they are categorised using prior conceptual knowledge. Emotion labels facilitate the learning of emotion concepts in children (Ogren & Sandhofer, 2022). Deficits in emotion recognition have been documented in semantic dementia patients (Lindquist et al, 2014); recent research on the semantic variant of primary progressive aphasia suggests that semantic knowledge guides not only emotion recognition but also valence processing (Bertoux et al, 2020).…”
mentioning
confidence: 99%
“…We considered labels for locations as intermediate because they do not have a single, spatially bounded object as referent and coded spatial and time terms as intermediate in line with previous evidence showing that spatio-temporal elements are the most concrete among abstract concepts 29 . Labels for perceptual and physiological inner states were taken as intermediate, in line with the idea that bodily states, and at a higher level of abstractness emotions, represent the first concepts children acquire that do not have a concrete referent 69 , 70 . Finally, we coded as high in abstractness words that are considered as such according to the current literature 26 , as words referring to numbers, emotions, and mental states terms, together with verbs and pronouns, typically considered as more abstract than nouns 71 – 73 , and words for routines that are considered as abstract in recent studies 31 .…”
Section: Methodsmentioning
confidence: 99%